The bureaucracy of empathy : law, vivisection, and animal pain in late nineteenth-century Britain - Shmuely, Shira, 1982- (Corpus juris (Ithaca, N.Y.), 2023)
"This book examines the implementation of the British Cruelty to Animals Act (1876) in its first three decades and analyzes how civil servants and scientists understood and co-constructed conceptions of animal pain"--